Α-Bisabolol Mitigates Colon Inflammation by Stimulating Colon PPAR-γ Transcription Factor: In Vivo and In Vitro Study. (13th April 2022) - Venkataraman, Balaji; Almarzooqi, Saeeda; Raj, Vishnu; Dudeja, Pradeep K.; Bhongade, Bhoomendra A.; Patil, Rajesh B.; Ojha, Shreesh K.; Attoub, Samir; Adrian, Thomas E.; Subramanya, Sandeep B.
Abstract : The incidence and prevalence of inflammatory bowel disease (IBD, Crohn's disease, and ulcerative colitis) are increasing worldwide. The etiology of IBD is multifactorial, including genetic predisposition, dysregulated immune response, microbial dysbiosis, and environmental factors. However, many of the existing therapies are associated with marked side effects. Therefore, the development of new drugs for IBD treatment is an important area of investigation. Here, we investigated the anti-inflammatory effects of α -bisabolol, a naturally occurring monocyclic sesquiterpene alcohol present in many aromatic plants, in colonic inflammation. To address this, we used molecular docking and dynamic studies to understand how α -bisabolol interacts with PPAR- γ, which is highly expressed in the colonic epithelium: in vivo (mice) and in vitro (RAW264.7 macrophages and HT-29 colonic adenocarcinoma cells) models. The molecular docking and dynamic analysis revealed that α -bisabolol interacts with PPAR- γ, a nuclear receptor protein that is highly expressed in the colon epithelium. Treatment with α -bisabolol in DSS-administered mice significantly reduced Disease Activity Index (DAI), myeloperoxidase (MPO) activity, and colonic length and protected the microarchitecture of the colon. α -Bisabolol treatment also reduced the expression of proinflammatory cytokines (IL-6, IL1 β, TNF- α, and IL-17A) at the protein and mRNA levels. The expression of COX-2 and iNOS inflammatory mediators were reduced along with tissue nitrite levels. Furthermore, α -bisabolol decreased the phosphorylation of activated mitogen-activated protein kinase (MAPK) signaling and nuclear factor kappa B (NF κ B) proteins and enhanced colon epithelial PPAR- γ transcription factor expression. However, the PPAR- α and β / δ expression was not altered, indicating α -bisabolol is a specific stimulator of PPAR- γ . α -Bisabolol also increased the PPAR- γ transcription factor expression but not PPAR- α and β / δ in pretreated in LPS-stimulated RAW264.7 macrophages. α -Bisabolol significantly decreased the expression of proinflammatory chemokines (CXCL-1 and IL-8) mRNA in HT-29 cells treated with TNF- α and HT-29 PPAR- γ promoter activity. These results demonstrate that α -bisabolol mitigates colonic inflammation by inhibiting MAPK signaling and stimulating PPAR- γ expression.